Review of Essential Oil Bioactivity Against Anxiety Symptom - Hery Prambudi; Supriyatin (Jurnal Penelitian Pendidikan IPA, 2025)
The use of essential oils as complementary therapy for various health conditions, especially those involving the central nervous system (CNS), is gaining increased attention. Anxiety disorder, a common CNS-related condition characterized by excessive worry and fear, is one of the main targets for such therapies. Essential oils from various plants contain bioactive compounds that act on the CNS and exhibit anxiolytic potential. This systematic literature review aimed to assess the anxiolytic bioactivity of essential oils and identify the most effective types used for anxiety reduction. Preclinical studies from seven journals revealed that essential oils such as Agarwood, Bergamot, Cananga odorata, Ocimum basilicum, Lavender, Nectandra grandiflora, and Cinnamon influence animal behavior linked to anxiety reduction. Clinical reviews from eleven studies found that Lavender oil, especially due to its linalool content, was the most commonly used essential oil for lowering anxiety levels. The mechanisms include inhibition of CRF, ERK1, and CREB, antagonism of NMDA receptors, inhibition of SERT, and modulation of GABAA receptors and calcium influx. In conclusion, essential oils exhibit various bioactivities affecting the CNS, supporting their role as potential anxiolytic agents.